Assuming the Ecosexual Position : The Earth as Lover - Sprinkle, Annie, 1954-; Klein, Jennie; Stephens, Beth (Book collections on Project MUSE., 2021)
"The story of the artistic collaboration between the originators of the ecosex movement, their diverse communities, and the Earth"--